“Cold Curing” of Polyethylene Glycol Maleate with Acrylic Acid and Some Physicochemical Properties of Their Solutions - Burkeyeva, G.K.; Tazhbayev, Ye.M.; Muslimova, D.M.; Nurseiit, G.D.; Zhaparova, L.Zh. (KU Publ., 2022)
The possibility of using the copolymers based on unsaturated polyesters with acrylic acid (AA) as the main component (polymeric basis) for the creation of novel highly effective sealants and glues of domestic production was demonstrated. Polyethylene glycol maleate (p-EGM) was synthesized by step-growth polymerization of maleic anhydride with ethylene glycol using the catalyst, which shortened the process duration. A number of solutions of p-EGM with AA were obtained. Physicochemical characteristics of initial solutions were determined. Some rheological properties of the solutions of p-EGM in unsaturated carboxylic acid were studied. Radical polymerization — the process of “cold curing” of the solutions of p-EGM with AA at room temperature was carried out. The combination of initiating a system of cold curing consisting of initiator (benzoyl peroxide) and promoter (dimethylaniline) was selected and their optimal content in the initial monomer mixture was established. The main parameters of curing, namely gelation time and curing time, were determined. Identification of the copolymers was performed using IR-spectroscopy. The morphology of the surfaces of cured samples of p-EGM with AA was studied using SEM. The optimal composition requiring further studies as highly filled compositional polymeric materials for using as sealants and glue basis was established.
Полиэтиленгликоль малеатын акрил қышқылымен «суық» қатайту және олардың ерітінділерінің кейбір физика-химиялық қасиеттері
«Холодное» отверждение полиэтиленгликольмалеината с акриловой кислотой и некоторые физико-химические свойства их растворов
Keywords: sealant; glue; unsaturated polyester; polyethylene glycol maleate; unsaturated carboxylic acid; acrylic acid; radical copolymerization; cold curing